Perspectivas para abordar la inteligencia artificial en la enseñanza de periodismo. Una revisión de experiencias investigadoras y docentes. - Gómez-Diago, Gloria (Revista Latina de Comunicación Social, 2022)
Introduction: In a context where media are increasingly using artificial intelligence (Neuman, 2021), and where this technology is absent in bachelor's and master's degrees in communication in Spain (Sanchez García; Calvo Barbero; Díez Gracia, 2021; Ufarte; Calvo; Murcia, 2020; Ufarte; Fieiras; Túñez, 2020). Methodology: We have located research projects and international teaching experiences addressing artificial intelligence and introducing it within journalism education. In addition, during the year 2021, we have participated in six national and international academic events addressing artificial intelligence within three areas of the field of communication: research, professional context, and university teaching. Results: The insights, the projects, and teaching initiatives obtained approach artificial intelligence fundamentally, from two angles, a critical perspective that pays attention to the social consequences of its use in the media context and an applied perspective aiming to train journalism students fundamentally in three competences: data collection and processing, automated content creation and content verification. Conclusions: Being scarce, the research and teaching initiatives available, they provide ways to introduce artificial intelligence in the curriculum of the degrees and masters in journalism and communication, from a critical perspective that taking into account what the media does, assumes the formative challenges derived from the use and extension of this technology.